Fractures of the Cuboid Bone: A Critical Analysis Review. Issue 4 (April 2020) - Engelmann, Esmee W.M.; Rammelt, Stefan; Schepers, Tim
Abstract : Cuboid fractures rarely occur in isolation, and a high index of suspicion for the presence of Chopart, Lisfranc, or complex midfoot injuries should be raised. The cuboid is the cornerstone of the lateral column and acts as a bridge between the lateral column and the transverse plantar arch. Its most important role is maintenance of lateral column length and associated motion in the midtarsal and tarsometatarsal joints. To date, a classification system that is validated for clinical practice (i.e., guidance for management and prediction of outcome and prognosis) is lacking. The principles of operative treatment are restoration of articular congruity, lateral column length, and stability of the Chopart and Lisfranc joints. Nonoperative management is reserved for nondisplaced articular fractures (<1 mm) or avulsion fractures that are caused by low-energy trauma.